Preserved fertility despite erectile dysfunction in mice lacking the nitric oxide receptor - Groneberg, Dieter (Blackwell Science Inc, 2013)
Nitric oxide (NO) and cGMP have been shown to be important mediators of penile erection. Erectile dysfunction may result from reduced or non-functional signal transduction within this cascade. There is, however, some inconsistency in the available data as mice lacking NO synthases (endothelial and neuronal nitric oxide synthase, or both) appear to be fertile whereas mice deficient in cGMP-dependent protein kinase I (PKGI) suffer from erectile dysfunction. To clarify this discrepancy we performed studies on mice lacking the NO receptor NO-sensitive guanylyl cyclase (NO-GC). In addition, we generated cell-specific NO-GC knockout (KO) lines to investigate the function of NO in individual cell types. NO-GC was specifically deleted in smooth muscle or endothelial cells (SM-guanylyl cyclase knockout (SM-GCKO) and EC-GCKO, respectively) and these KO lines were compared with total knockouts (GCKO) and wild-type animals. We investigated expression of NO-GC, NO-induced relaxation of corpus cavernosum smooth muscle and their ability to generate offspring. NO-GC-positive immunostaining was detected in smooth muscle and endothelial cells of murine corpus cavernosum but not in interstitial cells of Cajal. NO released from NO donors as well as from nitrergic neurons failed to relax precontracted corpus cavernosum from GCKO mice in organ bath experiments. Similar results were obtained in corpus cavernosum from SM-GCKO mice whereas deletion of NO-GC in endothelial cells did not affect relaxation. The lack of NO-induced relaxation in GCKO animals was not compensated for by guanosine 3′,5′-cyclic monophosphate (cGMP) signalling. To our surprise, GCKO males were fertile although their ability to produce offspring was decreased. Our data show that deletion of NO-GC specifically in smooth muscle cells abolishes NO-induced corpus cavernosum relaxation but does not lead to infertility.